PRODUKTIVITAS RUMPON PORTABLE MENGGUNAKAN PANCING ULUR DI PERAIRAN JEPARA - Roza Yusfiandayani; Desi Rezki Amelia; Mochammad Riyanto (Jurnal Teknologi Perikanan dan Kelautan, 2017)
The portable Fish Aggregating Devices (FADs) is an auxiliary fishing gear that can be operated on a multiple-time basis, as a fish-collecting device with an attractor. The purposes of the study are to determine the catch composition, length and weight frequency of the catch around portable FADs, determine the catch productivity of handlinearound FADs at the day and night time. The catch composition were consist of: kawakawa (Euthynnus affinis), short mackerel (Rastrelliger branchysoma), swordfish (Xiphias gladius), great barracuda (Sphyraena barracuda), and redbelly yellowtail fusilier (Caesio cuning). Total catch by handline was 160 individual. The length and weight relationship for dominant fish species was b<3 for Euthynnus affinis and Rastrelliger branchysoma (allometric negative) while b>3 for Xiphias gladius (allometric positive). The Mann Whitney U test shows that there was not significant different catch between day and night time operating hours.